A wearable low-power and low-cost electromyographic sensor for arm prosthesis - Haberman, Marcelo Alejandro (2020)
Abstract— This work presents the design considerations for an electromyographic (EMG) sensor destined to be integrated in a low-cost robotic arm prosthetic for below-elbow amputation, which is being developed in Paraguay by a multidisciplinary teamwork. The design exposed on this paper is addressed to optimize the embedded 14 bits ADC of the MSP432P401R microcontroller. It achieves the amplification and filtering of EMG signals with an input-referred noise of 1.35 μVRMS, and a CMRR greater than 95 dB, with a very low quiescent current consumption of 40 μA. The sensor also includes a common-mode feedback circuit that drives a reference electrode.